Ã£ÂÂ¿Ã£â€šâ€œÃ£ÂÂªÃ£ÂÂ®Ã¦â€”Â¥Ã¦Å“Â¬Ã¨ÂªÅ¾ I Ã§Â¬Â¬Ã¯Â¼â€˜Ã¨ÂªÂ²Ã£Ââ€¹Ã£â€šâ€°Ã§Â¬Â¬15Ã¨ÂªÂ²Ã£ÂÂ¾Ã£ÂÂ§Ã£ÂÂ®Ã¤Â¼Å¡Ã¨Â©Â±Ã£ÂÂ«Ã£ÂÅ Ã£Ââ€˜Ã£â€šâ€¹Ã¨Â¨â‚¬Ã¨ÂªÅ¾Ã¨Â¡Å’Ã¥â€¹â€¢Ã£ÂÂ®Ã¤Â½Â¿Ã§â€Â¨Ã¥Ë†â€ Ã¦Å¾Â (THE USE OF SPEECH ACT IN CONVERSATION OF MINNA NO NIHONGO I) - Diner, Lispridona (Language Circle: Journal of Language and Literature, 2009)
In conceying something we need so many expressions called manners. There are four kinds of manners: (1) Assertive manners, (2) Cognitive manners, (3) Expressive manners, and (4) Directive manners. The objective of this study is to describe the manners in Minna no Nihongo I’ book. The technique used in this study is done by collecting data related to activities of manners. Based upon the data, it could be concluded that in conveying something in conversation one has to use imperative expression, permissive expression and pragmatic expression. Key word: manner